Gravity, GPS and geomagnetic data in India - Tiwari, V.M.; Veenadhari, B.; Gahalaut, V.K.; Mukherjee, S.; Dimri, V.P. (My University, 2014)
Gravity, Global Positioning System (GPS) and Geomagnetic data sets in India are acquired by different research, academic and government institutions, under various projects. These data sets have extensively been utilized for natural resources and lithopsheric explorations, earthquake studies, atmospheric and ionospheric studies, control surveys, aircraft navigation, etc. The data are archived at individual institutions and have different modes of procurement considering some of the data, e.g., gravity data are classified in nature. Some of these data sets are contributed to the international observational network for example IGS and INTERMAGNET and are available as open source for the scientific communities. Present article provides information about different types of available Gravity, GPS and Geomagnetic data, their archival and mode of availability to the user community
Keywords: Global positioning system; Gravity; Geomagnetism; India; GPS